The intersection between transformational leadership and employee retention within smes in the services sector / Nor Sabrena Norizan...[et al.] - Norizan, Nor Sabrena; Abdul Rahman, Ramlee; Ismail, Irzan (Universiti Teknologi MARA, Kedah, 2019)
Many employees leave organization because of the leader. Thus, this study focuses on the intersection between transformational leadership and employee retention within SMEs in the services sector. SMEs in services sector located in Peninsular Malaysia has been chosen as the population due to its largest contribution to Malaysia economic growth. Transformational leadership styles are found to be the determinants of employee’s retention success and survival in every organization. Based on the previous study, the determinants of transformational leadership are found to be the factors that significantly influence on employees intention to stay. Analyzing transformational leadership styles on employee retention will give greater understanding on the employee shortage and thus helping the organization to develop potential initiatives to overcome the retention problems in SMEs. Therefore, this study intends to find out the influence of transformational leadership on employee retention within employees who works in SMEs within the services sector. From the past literature, it is found that transformational leadership significantly influences employee retention. Hence, it is oped that, from the perspective of Malaysia SMEs, the result of this study can embrace transformational leadership as a factor that can help to enhance staff retention in the organization.